PENGARUH FASILITAS LABORATORIUM DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR KOMPUTER AKUNTANSI (Dinamika Pendidikan, 2009)
The objectives of the study  areto know whether there are any influence of laboratory facilities and learning motivation toward students’ achievement in Computer Accounting for  XII grade Accounting’s Students in SMK Negeri 9 Semarang or not and to know the percentage of it.Population of this study was all students of XII grade Accounting Program in SMK Negeri 9 Semarang, the number were 82 students. The sample was all population involved Class Accounting I and Class Accounting II. Variables were laboratory facilities and learning motivation as independent variables and learning achievement in Accounting Computer as a dependent variable. Collecting the data used questionnnaire method and documentation, then analyzed by  percentage descriptive analysis and double- regression technique. Result of study showed there was a significant influence between laboratory facilities and learning motivation toward learning achievement in Accounting Computer, with regression equalityY = 23,540 + 0,503X1 + 0,178X2. From the data analysis, it was obtained Fhitungwas 150,299 higher than Ftabel = 3,112. It mean that hypothesis that statedthere was a significant influence between laboratory facilities and learning motivation toward learning achievement in Accounting Computer was accepted. Meanwhile, determination coefisien for R was 0,890 that showed that both laboratory facilities and learning motivation can influence learning achievement in Accounting Computer for 79.2%.Based on the result above, it is suggested for the schools to create a sufficient computer laboratory facilities and supporting books so students will get easy to study and can improve students’ achievement learning, for teachers and parents to give motivation for students so they can be motivated to study in improving learning achievement. Key words : Laboratory Facilities, Learning Motivation, Learning Achievement